Analisis Teks Deskripsi dalam Buku Paket Piwulangan Bahasa Jawa Muatan Lokal Wajib Jawa Tengah Kelas VIII - Kurnianingrum, Aprilia; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2022)
This study aims to (1) describe the types of folklore in Blora Regency, (2) discuss the structure of Blora Regency folklore, (3) explain the educational value contained in Blora Regency folklore.In this study using descriptive qualitative. This research provides detailed description and analysis of information. This research uses a single case study strategy which is carried out on one characteristic and one target (subject), namely the folklore of Blora Regency. The analysis technique used is interactive model of analysis.The folklore of Blora Regency is classified as legend, namely in individual legends and legends of the origin of a place. The storyline used in the folklore of Blora Regency is that humans are described as humans who have certain supernatural powers and are of good character. Place settings and social settings are more widely used in Blora Regency folklore and contain a fairly varied mandate. The educational values contained in Blora Regency folklore include the value of moral education, the value of traditional education, religious values, and the value of heroic education.